Gending Architectural Design of the Javanese Arts Performance Center in Wonogiri City, Central Java - Farras Anwar; Yuke Ardhiati (Journal of Aesthetics, Creativity and Art Management, 2023)
The aim of this study is to provide facilities for fans and performers of the arts, in the form of a building that is able to accommodate a number of local cultural arts activities that represent Wonogiri's local wisdom while at the same time being able to reflect technological advances so that they can embrace young people's interest in loving traditional culture. The approach used in the design is research-based design, and the study of architectural history, namely design that is supported by research results, regarding the wishes and expectations of residents for activities and facilities, which takes into account the history of the city, traditional buildings, patterns of life and culture of the community, to support the design. The results showed that the design consists of several zones of public, semi-public, semi-private, private, service, with 4 main room divisions including the main lobby room, main performance room, semi out door show room, and education and training room. The layout of the building, site, and external performance of the building are designed with a mix of cultures and illustrate the meaning of the name Wonogiri which means forest and mountain, which is combined with modern architecture.